ANALISIS KESEDIAAN PETANI PADI SAWAH DALAM MEMBAYAR JASA LAYANAN PENGELOLAAN IRIGASI DI DAERAH IRIGASI WAY KETIBUNG KABUPATEN LAMPUNG SELATAN - Fembriarti Erry Prasmatiwi; Raden Hanung Ismono; Tunjung Andarwangi (Universitas Galuh Ciamis, 2021)
Water is one of important things for the process of rice field farming. Irrigation as one of water sources for rice farming needs to be managed and maintained. The role of farmers is very important for irrigation management efforts. The contribution of farmers in the repair and management of irrigation can be realized in the form of willingness to pay (WTP) of irrigation management services. The benefit of paying for irrigation management services is that it can be used for better irrigation management and maintained water adequacy. This study aims to determine the value of willingness to pay from farmers that use irigation from the Way Ketibung’s Irigation Area in Lampung Selatan regency, and the factors influence it. Data collection was conducted in Sidomulyo and Candipuro district, Lampung Selatan in Juni - September 2020. The number of samples of this research is 100 farmers who used irrigation for rice farming selected by using propotionate random sampling method from total population of 1223 farmers. The data are analyzed using contingent valuation method (CVM) and ordinal logistic. Based on the research results, average WTP value of irrigation management service in the Way Ketibung’s Irigation Area was IDR97,400.00 /Year, or IDR48,700.00 /Planting Session. The factors that influenced were land area and farmer’s knowledge of irrigation function